2012
DOI: 10.1016/j.quascirev.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Man and megafauna in Tasmania: closing the gap

Abstract: Recent discussion on the late Pleistocene extinction of the Australian megafauna has revolved around interpretation of several key fossil sites in Tasmania. It has been suggested that humans did not arrive in Tasmania until after the megafauna became extinct, or did not hunt now extinct megafauna, and therefore that humans cannot be implicated in the extinctions. Radiocarbon results from these sites indicate that the youngest extinct megafauna are close to charcoal ages from the oldest archaeological deposits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Previous 14 C results on various collagen/gelatin fractions prepared from Zygomaturus trilobus and Palorchestes azael bones were scattered and considered unreliable by Gillespie et al . (). Based on geological data, Gill and Banks () suggested that the deposit containing the bones was >75 ka; radiocarbon ages on wood, marl and peat recovered from Mowbray Swamp (and similar fossiliferous deposits at the nearby Pulbeena Swamp) were consistently >50000 BP (Banks et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous 14 C results on various collagen/gelatin fractions prepared from Zygomaturus trilobus and Palorchestes azael bones were scattered and considered unreliable by Gillespie et al . (). Based on geological data, Gill and Banks () suggested that the deposit containing the bones was >75 ka; radiocarbon ages on wood, marl and peat recovered from Mowbray Swamp (and similar fossiliferous deposits at the nearby Pulbeena Swamp) were consistently >50000 BP (Banks et al .…”
Section: Resultsmentioning
confidence: 99%
“… Uncalibrated radiocarbon ages on XAD ‐2 purified total amino acid fractions (black solid circles) measured on extinct marsupials in this study, compared with previous results on collagen or gelatin (open circles, W hite & F lannery ) or ultrafiltered gelatin (grey‐filled circles, G illespie et al . ). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research there has shown that the combination of ecohydrological drought (exacerbate by anthropogenic soil drainage) and fire can cause the state change from rainforest to shrubland because the upper profile of organic soils are destroyed Taufik et al 2017). Also, unlike most tropical savannas (e.g., Skarpe 1992), no substantial populations of large herbivores graze on the Tasmanian sedgelands: whether the extinct Pleistocene marsupial megafauna (Gillespie et al 2012) were important in shaping the ecology (e.g., Gill 2014; Rule et al 2012) in this ecosystem is unknown.…”
Section: Resultsmentioning
confidence: 99%